Pengaruh Pemahaman Peraturan Perpajakan, Kesadaran Wajib Pajak dan Kompetensi Account Representative terhadap Penerimaan Pajak (Studi Kasus KPP Madya Makassar): (Studi Kasus KPP Madya Makassar) - Creschenthum Srimariastuti Boroh; Mursalim Mursalim (STIM LASHARAN JAYA MAKASSAR, 2018)
The influence of taxpayers understanding of bills of tax, awareness of taxpayers, and competency of the Account Representative to the tax revenue in Middle Tax Office of Makassar. The purpose of the research is to find out the influence of understanding of bills of taxes, awareness of taxpayers, and the competence of Account Representative in significantly influencing the tax revenue of Middle Tax Office of Makassar.The method used in this research is the descriptive method with surveys approach. In which, samples taken randomly with questioners then analyzed with double linear regression.The result of the research draws the variable of understandings of bill of taxes and the competence of the account representative that significantly influencing the tax revenue. And the awareness of taxpayers shows the other words.